New taxa and notes of some described species of scaly crickets (Orthoptera: Mogoplistidae: Mogoplistinae) from Singapore - Tan, Ming Kai; Ingrisch, Sigfrid (Zootaxa, 2013)
Two new species of Mogoplistinae from Singapore are described: Micrornebius kopisua sp. n. and Ornebius insculpta sp. n. The first record and description of males of Ornebius albipalpus Ingrisch, 2006 and females of Ornebius tampines Tan & Robillard, 2012 are given. The occurrence of Ornebius rufonigrus Ingrisch, 1987 in Singapore is confirmed while confirming the identity of another Ornebius species from Singapore with Ornebius cf. pullus Ingrisch, 2006 requires further investigation. A key to the species of Mogoplistinae from Singapore is provided.